Electrochemical behaviour of Ti6Al4V porous structures fabricated by powder metallurgy route - Maninder Singh; Amoljit Singh Gill; Parneet Kaur Deol (Journal of Electrochemical Science and Engineering, 2024)
In this investigation, the powder metallurgy process was used to fabricate porous structures of Ti6Al4V alloy by adding space holder powder particles. The samples were fabricated with varying levels of compaction pressure and other process parameters were kept unchanged in order to investigate the variation in electrochemical behaviour. It was observed that a lower level of compaction pressure resulted in an increase in corrosion current density and rate and a decrease in polarisation resistance. The sample's inability to achieve passivity against electrochemical corrosion, when fabricated using a lower level of compaction pressure, was linked to a higher number of interconnecting micropores. The results of the microstructure analysis confirmed the significant densification of the powder particles when higher compaction pressure was used. The study recommends that a compaction pressure of 300 MPa or higher may be used for fabricating porous structures for biomedical applications.